A chemically characterized ethanolic extract of Thai Perilla frutescens (L.) Britton fruits (nutlets) reduces oxidative stress and lipid peroxidation in human hepatoma (HuH7) cells - Narisara Paradee (2019)
© 2019 John Wiley & Sons, Ltd. Perilla frutescens is cultivated in East Asian countries including Thailand, and the nutlets (single-seeded fruits) are used as traditional and medicinal food. Perilla nutlets extracted by ethyl acetate (EA), 80% ethanol (Eth), and hot water (HW) sequentially were chemically characterized using high-resolution accurate liquid chromatography-mass spectrometry with the main compounds detected assigned as rosmarinic acid and derivatives of the flavones apigenin and luteolin, with the more diverse chemical composition observed with the Eth extract. All extracts showed dose-dependent free-radical scavenging activity, with the Eth extract the most potent (IC50 = 3.43 mg/ml for ABTS• scavenging and 0.27 mg/ml for DPPH• scavenging). The Eth extract also inhibited AAPH-induced hemolysis (IC50 = 0.07 mg/ml) more potently than did the HW (IC50 = 0.38 mg/ml) and EA extracts (IC50 = 1.63 mg/ml). An MTT test revealed all the extracts were noncytotoxic at concentrations up to 200 μg/ml. Only the Eth and EA extracts showed protective effects against the generation of reactive oxygen species and lipid peroxidation in FeCl3-induced HuH7 cells in a dose-dependent manner. Our findings suggest the Eth extract of Thai perilla nutlets, containing rosmarinic acid and flavones and their derivatives, may have potential to provide protection against oxidative stress in hepatic disorders.